Re-evaluating albumin use in traumatic brain injury - Jean-Louis Vincent; Ricard Ferrer; Fabio S. Taccone; Christian J. Wiedermann; Peter Reinstrup (Journal of Intensive Care)
Abstract Traumatic brain injury (TBI) affects approximately 69 million people annually, with the majority of cases being mild-to-moderate in severity. However, in severe TBI, early management is critical and includes fluid resuscitation to control intracranial pressure (ICP) and optimize cerebral perfusion pressure. The SAFE-TBI study linked hypotonic 4% albumin to higher mortality versus saline (33.2% vs. 20.4%; RR 1.63; P = 0.003), likely due to elevated ICP, prompting guidelines favoring saline. However, these recommendations are based on low-quality evidence and overlook hyperoncotic albumin. Preclinical data confirm that hypotonicity—not albumin—drives ICP elevation. Emerging data suggest that hyperoncotic albumin (20–25%) may reduce ICP and improve outcomes. This letter highlights evidence gaps and advocates re-evaluating albumin use in TBI, especially hyperoncotic formulations.